A method for rapid polymerization drying of organic coatings

CN122938004APending Publication Date: 2026-10-20SHANGHAI DAODUNSCIENCE & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611140005.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-20

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to a rapid polymerization and drying method for organic coatings, belonging to the field of infrared radiation materials and coating curing technology. This invention utilizes the special infrared radiation emitted by infrared resonant functional ceramic materials. Photons carry energy and penetrate into the coating, directly acting on water molecules and coating components, providing direct and uniform heating from within the coating. This significantly improves energy transfer efficiency, reduces energy consumption, and shortens drying time. This method has low requirements for substrate preparation, reduces the impact of environmental factors during construction, greatly improves construction efficiency, and enhances coating quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of infrared radiation materials and coating curing technology, and relates to a method for rapid polymerization and drying of organic coatings. Background Technology

[0002] Coating film formation refers to the process by which a coating, after being applied to a substrate surface, forms a dense and complete solid film through physical or chemical action. This process is commonly referred to as coating drying and curing. The quality of the coating film directly determines its protective performance and decorative effect.

[0003] Based on different drying mechanisms, existing coating drying methods can be mainly divided into three categories: natural drying, hot air drying, and radiation curing.

[0004] Natural drying is the most traditional drying method, which relies on solvent evaporation or oxidative cross-linking at ambient temperature to form a film. Its advantages are simple equipment and convenient operation, but it has obvious defects such as slow drying speed, great influence from ambient temperature and humidity, and difficulty in controlling coating quality, making it difficult to meet the efficiency requirements of industrial production.

[0005] Hot air drying is currently the most widely used industrial drying method. It uses convection heating to raise the temperature of the coating, accelerating solvent evaporation or cross-linking reactions. However, this drying method has inherent technical bottlenecks: heat is transferred from the coating surface to the interior, causing the surface to dry preferentially, forming a surface-dried layer. This surface-dried layer hinders the evaporation of internal solvents or moisture, easily leading to defects such as pinholes, blistering, and orange peel. Furthermore, the thicker the coating, the longer the drying time and the higher the energy consumption. Especially in the automotive painting industry, whole-vehicle baking typically uses high-power bulbs for convection heating, which suffers from high energy consumption, low efficiency, and significant pollution.

[0006] Radiation curing technology mainly includes ultraviolet (UV) curing and infrared (IR) curing. UV curing utilizes ultraviolet light to initiate the generation of free radicals or cations from photoinitiators, achieving rapid cross-linking of the coating. It has the advantages of fast curing speed and low energy consumption. However, its application is limited to photocurable coatings, and it suffers from curing dead zones for opaque coatings, colored coatings, or complex-shaped workpieces, making deep curing difficult. Infrared curing uses infrared radiation to heat the coating, offering certain advantages over hot air drying. However, traditional infrared drying technology mainly uses infrared lamps or quartz tubes as radiation sources, which have a broad but uncontrollable radiation spectrum and low energy density (typically a few to tens of W / cm²). 2 (At the scale of the heat transfer level), the heating rate is slow, and the heat transfer mainly acts on the coating surface, making it difficult to solve the problem of uneven drying from the surface to the interior. Moreover, the drying effect is not ideal for environmentally friendly coatings such as water-based coatings.

[0007] Water-based coatings, due to their low volatile organic compound (VOC) content, have become an important development direction in the coatings industry. However, the high latent heat of vaporization and slow evaporation rate of water in water-based coatings place higher demands on drying technology. Currently, water-based coatings still mainly rely on natural drying and hot air drying, which suffers from particularly prominent problems of low drying efficiency and high energy consumption.

[0008] In the automotive painting industry, coating performance requirements are extremely stringent: not only must they possess excellent mechanical properties, high fullness, and high gloss, but they also need superior adhesion, hardness (typically between B and 3H), scratch resistance, weather resistance, and chemical resistance. Automotive paint typically employs a baking-curing process. After welding repairs to the vehicle frame, the paint undergoes primer dipping, drying, and then electrostatic spraying of the topcoat in a cleanroom, finally being baked and cured at approximately 200°C. This process is energy-intensive, and during repairs and touch-ups, the inability to perform high-temperature baking and the long curing time at room temperature severely impact repair efficiency, becoming a major technical pain point in the automotive aftermarket.

[0009] Therefore, there is an urgent need to develop a new technology that can achieve rapid, uniform, and low-energy drying of coatings to improve coating efficiency, enhance coating quality, and reduce energy consumption. Summary of the Invention

[0010] The purpose of this invention is to provide a method for rapid polymerization and drying of organic coatings. This invention utilizes the special infrared radiation emitted by infrared resonance functional ceramic materials, which carries energy through photons to penetrate into the interior of the coating and directly act on water molecules and coating components, uniformly heating from the inside of the coating, thereby greatly improving energy transfer efficiency, reducing energy consumption, and shortening drying time.

[0011] The objective of this invention can be achieved through the following technical solutions: A rapid polymerization and drying method for organic coatings, the method utilizing infrared resonant functional ceramic materials as an infrared radiation source, includes the following steps: S1. Applying the coating to the surface of a substrate to form a coating to be dried, wherein the substrate surface is an untreated surface with oil, rust and / or water, or a surface that has been sandblasted to remove rust; S2. The coating is placed in the infrared radiation region, which is made of infrared resonant functional ceramic material. After being excited, the infrared resonant functional ceramic material can emit infrared photons with a wavelength of 3~12μm. S3, to make the infrared photons have an energy density of up to 320 W / cm². 2 The energy density is irradiated onto the surface of the coating to be dried, and the energy density is reached within 12 microseconds; S4. Maintain irradiation to allow the infrared photons to penetrate the coating, thereby achieving solid drying of the coating.

[0012] As a preferred embodiment of the present invention, the infrared resonant functional ceramic material is composed of a base material and a rare earth dopant, wherein the base material includes SiO2, Fe2O3, CaO, Al2O3, MgO, CuO, and Cr2O3, and the rare earth dopant is one of LaCrO3 and CeO2.

[0013] As a preferred embodiment of the present invention, the mass percentages of the base material and rare earth dopant are: 25~30% Fe2O3, 15~17% SiO2, 5~5.5% CaO, 2~2.5% Al2O3, 1~2% MgO, 0.2~0.4% CuO, 40~45% Cr2O3, and 1~2% rare earth dopant.

[0014] As a preferred embodiment of the present invention, the preparation process of the infrared resonance functional ceramic material is as follows: The base material and rare earth dopant are mixed and ball-milled with Teflon balls as the grinding medium to obtain fine powder. After drying, the powder is pressed into shape and then sintered in air at 1900~2500℃. After sintering, the infrared resonance functional ceramic material is obtained by crushing and grinding.

[0015] As a preferred embodiment of the present invention, the coating is one of water-based coating, single-component organic coating, and single-component powder coating.

[0016] As a preferred embodiment of the present invention, the substrate is one of metal, wood, plastic, glass or ceramic.

[0017] As a preferred embodiment of the present invention, the energy used during the excitation is one of electrical energy, solar thermal energy, steam thermal energy, industrial waste heat, or natural gas combustion thermal energy.

[0018] As a preferred embodiment of the present invention, the energy density of the infrared photons can reach up to 320 W / cm². 2 .

[0019] As a preferred embodiment of the present invention, the actual drying time is 10~600s.

[0020] As a preferred embodiment of the present invention, the emission spectrum of the infrared photons matches the infrared absorption spectrum of water molecules and / or resin molecules in the coating, wherein the main radiation peak of the infrared photons is located in the range of 2.7~3.3μm and 6.0~7.0μm of the OH bond stretching vibration absorption peak of water molecules.

[0021] As a preferred embodiment of the present invention, the distance between the infrared radiation area and the coating surface is 5~30cm.

[0022] An application of a rapid polymerization and drying method for organic coatings in the rapid curing of water-based intermediate or topcoat layers in automotive painting production lines.

[0023] The beneficial effects of this invention are: (1) This invention uses infrared resonance functional ceramic materials, which can generate a narrow-frequency pulse infrared light as needed. The frequency of the infrared light is approximately the same as that of water molecules or organic coatings. The pulse energy causes the water molecules (hydrogen bonds) or molecular bonds in the coating monomers to resonate, resulting in the breaking of hydrogen bonds and the polymerization of coating monomer molecules. Since the energy of infrared resonance directly penetrates into the interior of the coating and acts quickly on the water molecules, it causes the hydrogen bonds between molecules to break, making it easier for water molecules to detach. Therefore, the coating drying temperature is low, the speed is fast, the energy efficiency is high, and the energy consumption is low. Compared with the traditional drying method, the speed can be increased tenfold, and the energy consumption is only one-fifth of the traditional method, achieving the effect of energy saving and emission reduction, thereby expanding the application space of water-based coatings.

[0024] (2) By adjusting the energy density of infrared resonance, the length and three-dimensional structure of monomer polymer chains can be controlled, thereby obtaining coatings with properties different from those of conventional drying methods. This method can produce coatings with superior performance, improve coating quality, and overturn the approach of improving coating performance solely by improving polymer monomer materials and additives, thereby expanding the application field of powder coatings.

[0025] (3) The present invention has low requirements for substrate treatment, which can reduce the impact of construction environment factors, greatly improve construction efficiency, and improve coating quality. The drying method of the present invention can be widely used in industries such as sludge drying, high-salt wastewater treatment, waste battery treatment, wood dehydration, and food drying; the drying polymerization technology can be used in industries with high requirements for coating properties, such as the automotive industry, pipeline industry, and furniture industry. Detailed Implementation

[0026] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.

[0027] It should be noted that, unless otherwise specified, the present invention does not specifically limit the source of the raw materials used in the following embodiments. Commercially available products or products prepared by conventional preparation methods that are well known to those skilled in the art can be used. Experimental methods that do not specify specific conditions are all conventional methods and conventional conditions well known in the art.

[0028] Example 1

[0029] The paint used is automotive paint, brand name: PPG Hemmerat Black Automotive Paint, black primer (batch number: 03332190987), clear topcoat Hitech 3.0 (batch number: 331639260).

[0030] The infrared resonance functional ceramic material used consists of the following raw materials in the following mass percentages: 28% Fe2O3, 17% SiO2, 5.5% CaO, 2.5% Al2O3, 2% MgO, 0.3% CuO, 43.7% Cr2O3, and 1% LaCrO3.

[0031] The above raw materials were placed in a plastic-lined planetary mill and ball-milled for 8 hours using Teflon balls as the grinding medium to obtain finely ground powder. The powder was dried at 100°C for 4 hours to obtain dried powder. The dried powder was pressed into shape under a pressure of 80 MPa to obtain a green body. The green body was placed in a high-temperature furnace and sintered at 1950°C at a rate of 5°C / min in an air atmosphere for 3 hours. After sintering, the furnace was cooled to room temperature. The sintered body was then crushed, ground, and passed through a 200-mesh sieve to obtain infrared resonance functional ceramic material.

[0032] S1. Apply the coating to the surface of the substrate to form a coating to be dried. The substrate is a cold-rolled steel plate. S2. The coating is placed in the infrared radiation region, which is powered by a radiation plate made of the infrared resonant functional ceramic material prepared above. The vertical distance between the radiation plate and the coating surface is 15cm. After being excited by electrical energy, the infrared resonant functional ceramic material can emit infrared photons with a wavelength of 3~12μm. S3, once activated, infrared photons achieve an energy density of 320 W / cm². 2 The energy density is irradiated onto the coating surface to be dried, and the energy density reaches this level within 12 microseconds; S4. Maintain irradiation to allow the infrared photons to penetrate the organic coating, thereby achieving complete drying of the coating.

[0033] Example 2

[0034] The process is basically the same as in Example 1, except that the infrared resonance functional ceramic material in this example contains the following raw materials by mass percentage: Fe2O3 26%, SiO2 17%, CaO 5.5%, Al2O3 2.5%, MgO 2.0%, CuO 0.4%, Cr2O3 44%, and rare earth dopant (CeO2) 2.0%. The preparation method is the same as in Example 1, the sintering temperature is 2050℃, and the holding time is 2.5h. The coating used is a water-based coating (HB-6301 water-based acrylic polyurethane automotive topcoat), and the substrate is an aluminum alloy plate (treated by sandblasting and rust removal).

[0035] Example 3

[0036] The process is basically the same as in Example 1, except that the infrared resonance functional ceramic material in this example contains the following raw materials by mass percentage: Fe2O3 30%, SiO2 15%, CaO 5.0%, Al2O3 2.0%, MgO 1.0%, CuO 0.2%, Cr2O3 45%, and rare earth dopant (LaCrO3) 1.0%. The preparation method is the same as in Example 1, the sintering temperature is 2000℃, and the holding time is 3h. The coating is a single-component powder coating (epoxy polyester powder coating, RAL 5023), and the substrate is oak wood board.

[0037] Comparative Example 1 The comparison example is basically the same as Example 1, except that a traditional quartz infrared lamp (power of 2kW, emission wavelength range of 1~15μm) is used for drying, the distance between the radiator and the coating surface is 15cm, and continuous irradiation is carried out until the coating is completely dry.

[0038] Comparative Example 2 This comparative example is basically the same as Example 1, except that it uses a hot air circulating drying oven with a set temperature of 80°C and a wind speed of 3m / s, and is continuously dried until the coating is completely dry.

[0039] Comparative Example 3 This comparative example is basically the same as Example 1, except that it uses a common alumina ceramic plate as the infrared radiator, with an emission wavelength range of mainly 8~15μm and an energy density of 150W / cm². 2 The time from startup to reaching that energy density is 50 microseconds.

[0040] Comparative Example 4 The comparison example is basically the same as Example 1, except that the infrared resonance functional ceramic material contains the following raw materials by mass percentage: Fe2O3 40%, SiO2 10%, CaO 3%, Al2O3 8%, MgO 5%, CuO 1%, Cr2O3 33% (the composition ratio deviates from the scope of this invention and does not contain rare earth dopants).

[0041] Performance testing The coatings of the examples and comparative examples were tested according to ASTM D6675-01(2019) and enterprise standards VW TL 226 and GM 9504P. The test results are shown in the table below:

[0042] Based on the test data above, compared with Comparative Example 1, the product obtained in Example 1 has improved microhardness by 27%, erosion resistance by 79%, anti-friction fading performance by 31%, resistance to sap erosion by 44%, resistance to trypsin erosion by 69%, and acid resistance (H2SO4) by 10%.

[0043] Furthermore, the drying temperature in Comparative Example 1 was 140°C, while in Example 1 it was reduced to 95~110°C; the drying time of the primer in Example 1 was shortened from 20 min in Comparative Example 1 to 1 min, the drying time of the topcoat was shortened from 30 min in Comparative Example 1 to 6 min, the overall drying process was shortened from 50 min to 7 min, the efficiency was increased by 7 times, and the energy consumption was 20% of that using the traditional method.

[0044] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for rapid polymerization and drying of an organic coating, characterized in that, The method utilizes infrared resonant functional ceramic materials as an infrared radiation source, and includes the following steps: S1. Applying the coating to the surface of a substrate to form a coating to be dried, wherein the substrate surface is an untreated surface with oil, rust and / or water, or a surface that has been sandblasted to remove rust; S2. The coating is placed in the infrared radiation region, which is made of infrared resonant functional ceramic material. After being excited, the infrared resonant functional ceramic material can emit infrared photons with a wavelength of 3~12μm. S3, to make the infrared photons have an energy density of up to 320 W / cm². 2 The energy density is irradiated onto the surface of the coating to be dried, and the energy density is reached within 12 microseconds; S4. Maintain irradiation to allow the infrared photons to penetrate the coating, thereby achieving complete drying of the coating.

2. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The infrared resonance functional ceramic material is composed of a base material and rare earth dopants, wherein the base material includes SiO2, Fe2O3, CaO, Al2O3, MgO, CuO, and Cr2O3, and the rare earth dopants are one of LaCrO3 and CeO2.

3. The rapid polymerization and drying method for organic coatings according to claim 1 or 2, characterized in that, The mass percentages of the base material and rare earth dopant are: 25~30% Fe2O3, 15~17% SiO2, 5~5.5% CaO, 2~2.5% Al2O3, 1~2% MgO, 0.2~0.4% CuO, 40~45% Cr2O3, and 1~2% rare earth dopant.

4. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The preparation process of the infrared resonance functional ceramic material is as follows: The base material and rare earth dopant are mixed and ball-milled with Teflon balls as the grinding medium to obtain fine powder. After drying, the powder is pressed into shape and then sintered in air at 1900~2500℃. After sintering, the infrared resonance functional ceramic material is obtained by crushing and grinding.

5. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The coating is one of water-based coatings, single-component organic coatings, and single-component powder coatings.

6. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The substrate is one of metal, wood, plastic, glass or ceramic.

7. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The energy source used during the excitation is one of the following: electrical energy, solar thermal energy, steam thermal energy, industrial waste heat, or natural gas combustion thermal energy.

8. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The energy density of the infrared photons can reach up to 320 W / cm². 2 .

9. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The actual working time is 10~600s.

10. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The emission spectrum of the infrared photons matches the infrared absorption spectrum of water molecules and / or resin molecules in the coating, wherein the main radiation peak of the infrared photons is located in the range of 2.7~3.3μm and 6.0~7.0μm of the OH bond stretching vibration absorption peak of water molecules.

11. The rapid polymerization and drying method for organic coatings according to claim 1, characterized in that, The distance between the infrared radiation area and the coating surface is 5~30cm.

12. The application of the rapid polymerization and drying method for organic coatings according to any one of claims 1-11 in the rapid curing of water-based intermediate coatings or topcoats in an automotive coating production line.